Hassles and Panacea to Educational Researches in South- South Nigeria - Isaac, Dokubo N.; Isaac, Dokubo Chivuikem (European Scientific Journal, ESJ, 2016)
This study examined the problems affecting educational researches in South-South Nigeria. The research work was conducted at the University of Port Harcourt, Rivers state (UNIPORT); Niger Delta University, Amasoma, Bayelsa state (NDU); and the University of Calabar, Cross Rivers state (UNICAL). Descriptive survey research design was used for the study. The population for the study was 3000 which comprised of final year students and academic staff in the above mentioned institutions. A sample size of 600 was drawn from the population. Four research questions guided the study. A 30- item questionnaire was developed and administered. The study revealed governmental factors, tertiary institutional factors, and researchers’ factors affecting educational researches in South-South Nigeria. Recommendations were made such as: the various state governments should improve on the security condition in their respective regions; the managements of the South- South tertiary institutions should encourage lecturers to carry out researches by making funds available to them through Tertiary Education Trust (TET) fund; e-libraries should be introduced, etc.